Game Changer in Payment Method: Factors Influencing Users Intention to Use QRIS - Halley Christoforus Rettob; Batara Maju Simatupang; R. Bambang Budhijana; Antyo Pracoyo (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2026)
Payment system has undergone continuous changes, and the evolving landscape shows how QRIS (Quick Response Code Indonesia Standard) is changing Indonesian society preference of payment. The study explores the driving factors of users’ intention to adopt the QRIS through the lens of modified UTAUT framework to see whether users’ emotions correlate toward their Intention. Analysis is done through quantitative descriptive approach using PLS-SEM, with data collected from 109 QRIS users in the Greater Jakarta (Jabodetabek) area using a non-probability convenience sampling technique. The results show that Behavioral Intention has a significant effect on Intention to Use and bridges (mediates) the relationships between Social Influence, Effort Expectancy, and Performance Expectancy toward Intention to Use. In contrast, direct effects from Social Influence, Effort Expectancy, and Performance Expectancy have limited significance on Intention to Use. These findings suggest that QRIS adoption operates as a behavioral-driven process, highlighting the importance of strengthening users’ Behavioral Intentions to accelerate digital payment adoption. The study contributes to the digital payment literature by positioning QRIS as a transformative innovation in Indonesia’s payment system.